La mediazione tecnica nel conflitto fra le due immagini del mondo. Sellars, Husserl e l’estensione della mente - Manca, Danilo (Bollettino Filosofico, 2023)
In this article, I will reflect on the use of technology in scientific investigation. My aim is to understand the extent to which such reflection can contribute to the dispute between the manifest and the scientific image of man in the world. I will begin by pointing out the aporias underlying Sellars’s arguments, thus comparing them with Husserl’s theses on how the “technization” of knowledge breaks with the life-world. In light of this, in the second part of the essay, I will firstly consider how Ihde’s critique of Husserl’s concealment of the role of the technology of science meets with the theory of niche construction; secondly, I will focus on the sense in which we can describe language as a tool (or artefact) according to the extended approach to mind. Keywords: Language as a Tool, Life-World, Technological Mediation, The Extended Mind